Beyond success stories: learning from behavioral interventions in zoo conservation fundraising - Neves, Joao; Leong, Kristina; Correia, Inês (Frontiers in Conservation Science, 2025)
BackgroundEfforts to stem the species extinction crisis have been hampered by lack of funding. While public investment is key, private donations play an important role in wildlife conservation.ObjectiveThis study investigated whether persuasion techniques in bird show scripts could increase pro-conservation behavior at Zoomarine Algarve.MethodsAn initial exploratory study compared control and modified tropical bird show scripts using three persuasion strategies (“identifiable victim”, “anchoring effect”, and “bandwagon effect”), measured by conservation bracelet sales. The main study then focused on the “identifiable victim” effect, involving 116 sampling days in two conditions during summer 2023, with 148,545 visitors.ResultsThe exploratory study showed the modified script unexpectedly decreased sales. The main study found no significant difference in bracelet sales between conditions (Z = -.60, p = .55).ConclusionsThis research suggests complexities of applying persuasion techniques in field experiments and underscores the need for proper evaluation for informed decisions. The study provides insights into communication barriers and factors influencing conservation engagement in zoos, underlining the importance of communicating null results for advancing scientific understanding.